Longer Prehospital Time Decreases Reliability of Vital Signs in the Field: A Dual Center Study. Issue 6 (June 2021) - Schellenberg, Morgan; Biswas, Subarna; Bardes, James M.; Trust, Marc D.; Grabo, Daniel; Wilson, Alison; Inaba, Kenji
Background: Field vital signs are integral in the American College of Surgeons (ASA) Committee on Trauma (COT) triage criteria for trauma team activation (TTA). Reliability of field vital signs in predicting first emergency department (ED) vital signs, however, may depend upon prehospital time. The study objective was to define the effect of prehospital time on correlation between field and first ED vital signs. Methods: All highest level TTAs at two Level I trauma centers (2008-2018) were screened. Exclusions were unrecorded prehospital vital signs and those dead on arrival. Demographics, prehospital time (scene time + transport time), injury data, and vital signs were collected. Differences between field and first ED vitals were determined using the paired Student's t test. Propensity score analysis, adjusting for age, sex, injury severity score (ISS), and mechanism of injury compared outcomes among patients with ISS ≥16. Multivariate linear regression determined impact of prehospital time on vital sign differences between field and ED among propensity-matched patients. Results: After exclusions, 21 499 patients remained. Mean prehospital time was 32 vs. 41 minutes ( P < .001). On propensity score analysis, longer prehospital time was associated with significantly greater differences in systolic blood pressure (SBP) ( P < .001), pulse pressure (PP) ( P = .003), and Glasgow Coma Scale (GCS) ( P < .001). On multivariate analysis, linear regression that demonstrated longer prehospital time was associated with greater differences in SBP, heart rate (HR), and PP ( P < .001). Conclusions: Field vital signs are less likely to reflect initial ED vital signs when prehospital times are longer. Given the reliance of trauma triage criteria on prehospital vital signs, medical providers must be cognizant of this pitfall during the prehospital assessment of trauma patients.